2020
DOI: 10.1002/cbic.202000705
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Understanding of the Electron Transfer Pathway of Cytochrome P450s

Abstract: Cytochrome P450s are heme‐thiolate enzymes that participate in carbon source assimilation, natural compound biosynthesis and xenobiotic metabolism in all kingdoms of life. P450s can catalyze various reactions by using a wide range of organic compounds, thus exhibiting great potential in biotechnological applications. The catalytic reactions of P450s are driven by electron equivalents that are sourced from pyridine nucleotides and delivered by cognate or matching redox partners (RPs). The electron transfer (ET)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 136 publications
(116 reference statements)
0
28
0
4
Order By: Relevance
“…Heme proteins, including a series of monooxygenases, [6,7] peroxygenases [8] and peroxidases, [9,10] are proven effective in direct functionalization of alkyl, aryl, benzyl and allyl C−H bonds. Chloroperoxidase (CPO), a heme‐thiolate peroxidase from Caldariomyces fumago , is of particular interest for catalyzing C−H bonds by halogenation and hydroxylation [9,11,12] because it utilizes H 2 O 2 as both oxygen and electron donor thereby circumventing the concomitant regeneration of flavoproteins and cofactors [13] . In addition to enhancing the intrinsic activity through molecular modification, it is necessary to improve the operational stability of CPO for industrial application.…”
Section: Introductionmentioning
confidence: 99%
“…Heme proteins, including a series of monooxygenases, [6,7] peroxygenases [8] and peroxidases, [9,10] are proven effective in direct functionalization of alkyl, aryl, benzyl and allyl C−H bonds. Chloroperoxidase (CPO), a heme‐thiolate peroxidase from Caldariomyces fumago , is of particular interest for catalyzing C−H bonds by halogenation and hydroxylation [9,11,12] because it utilizes H 2 O 2 as both oxygen and electron donor thereby circumventing the concomitant regeneration of flavoproteins and cofactors [13] . In addition to enhancing the intrinsic activity through molecular modification, it is necessary to improve the operational stability of CPO for industrial application.…”
Section: Introductionmentioning
confidence: 99%
“…The structural comparison showed that the TDO contained an extra domain (gray part). In previous research, a "swing domain model" of P450BM3 FMN-binding domain operated the back-and-forth motions, which was governed by a flexible hinge domain (Chen et al, 2020). That implied that TDO-Fdx might swing to a favorable position to carry out the effective electron transfer from FAD to [2Fe-2S] cluster (Figure 2a).…”
Section: Structural Analysis Of Reductase Tdo and Prfmentioning
confidence: 91%
“…The reduced Fdx transfers the electron to the active center of the oxygenase to support the activation of dioxygen for biphenyl dihydroxylation. Self-sufficient P450 monooxygenases are highly active and convenient systems without partner reductase (Chen et al, 2020). The crystal structure of the self-sufficient P450 enzyme CYP116B46 has indicated that it contains the cofactor FMN to capture electrons from NADPH and RP Fdx, which has most efficient electron transfer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In eukaryotes, they are usually bound to membranes, whereas bacterial members appear freely in the cytosol. They contribute a major part in carbon source assimilation, production of secondary metabolites and metabolism of xenobiotics (Chen et al 2021). P 450 s have different sizes, cofactors and electron donors as well as various shapes of substrate binding pockets.…”
Section: Modification Of Cdps By Tailoring Enzymesmentioning
confidence: 99%